2023
DOI: 10.3390/s23125711
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Optomechanical Sensors—Integrating Diffractive Optical Structures for Enhanced Sensitivity

Abstract: The term optomechanical sensors describes devices based on coupling the optical and mechanical sensing principles. The presence of a target analyte leads to a mechanical change, which, in turn, determines an alteration in the light propagation. Having higher sensitivity in comparison with the individual technologies upon which they are based, the optomechanical devices are used in biosensing, humidity, temperature, and gases detection. This perspective focuses on a particular class, namely on devices based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 144 publications
(243 reference statements)
0
0
0
Order By: Relevance
“…Various types of optical fibers exist today: bowtie, elliptical, pseudo-rectangle, elliptical core, panda [13,14] and others [15][16][17]. However, the process of developing improved types of designs does not stand still [18][19][20].…”
Section: Problem Contextmentioning
confidence: 99%
“…Various types of optical fibers exist today: bowtie, elliptical, pseudo-rectangle, elliptical core, panda [13,14] and others [15][16][17]. However, the process of developing improved types of designs does not stand still [18][19][20].…”
Section: Problem Contextmentioning
confidence: 99%
“…Volume holographic diffraction gratings have been demonstrated previously as effective sensors for VOCs [15] the doping of the photopolymer matrix with zeolite nanoparticles has been demonstrated as a method of further enhancing the sensitivity of holographic VOC sensors [16], [17]. It has been demonstrated that coupling optical detectors, including holographic sensors with a mechanical transducer to form an optomechanical sensor enhances the sensitivity of both methods of transducing when comparing each of the methods in isolation [18] Previously, an optomechanical holographic sensor has been presented in the form of a bilayer cantilever sensor with demonstrated sensitivity for relative humidity [19], [20]. Recently, this device has undergone initial testing for sensitivity to VOCs, with the cantilever configuration demonstrating enhanced sensitivity to both air and ethanol when compared with a holographic grating recorded in a polymer layer coated a on glass slide (fixed grating) [21] However, challenges remain with the cantilever configuration presenting issues in terms of stability, repeatability and cross-sensitivity to other environmental analytes.…”
Section: Introductionmentioning
confidence: 99%